Rasio Keuangan Versus Rasio Pasar Untuk Peningkatan Nilai Perusahaan Food Dan Beverage - Dian Prawitasari; Ana Kadarningsih; Nanda Budi Kurniasih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Company performance can be seen from financial ratios and market ratios. High financial ratios and market ratios will attract investor interest, thereby increasing company value. This research has two objectives, namely looking at the influence of financial ratios on company value and analyzing the influence of market ratios on company value in the food and beverage sector. The research sample consisted of 120 annual financial data from 30 food and beverage sector companies listed on IDX consecutively from 2019-2022. The analysis method uses multiple regression tests and classical assumptions with SPSS as an analysis tool. Financial ratios are measured from three ratios, namely the solvency ratio, profitability ratio and liquidity ratio. The market ratio is measured from earnings per share or EPS. The research results show that only financial ratios as measured by profitability ratios can influence company value positively and significantly, while other financial ratios have no effect on company value. The market ratio relationship shows significant and negative influence on company value.